Pengaruh E-Service Quality, Perceived Usefulness dan Kepercayaan Terhadap Kepuasan Pengguna Transportasi Go-jek di Kota Malang - Mutmainah, Izrotul Ally; Hidayati, Nur; Dianawati, Eris (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to investigate how e-service quality, perceived usefulness, and trust impact the satisfaction levels  of Gojek transportation users in Malang  City. It employs  a quantitative approach to analyze the relationship between independent variables (e-service quality, perceived usefulness, and trust) and the dependent variable (satisfaction). The study's sample comprises 80 consumers from the Lowokwaru District in Malang City, and primary data collection is done through questionnaire distribution, aided by the SPSS data analysis tool. The findings of this study reveal that e-service quality, perceived usefulness, and trust collectively and significantly influence the satisfaction levels of Gojek transportation users in Malang City. The coefficient of determination test indicates that 54.6% of the variance in satisfaction can be explained by these variables, with the remaining 45.4% attributed to factors not investigated in this study. Keywords: E-Service Quality, Perceived Usefulness, Trust, and User Satisfaction